ANALISIS PENGUKURAN KINERJA RUMAH SAKIT DENGAN PENERAPAN METODE BALANCED SCORECARD (Studi Kasus Pada RSUD â€œKanjuruhanâ€ Kepanjen Kabupaten Malang) - Anisak, Laila Yulita; Affandy, Didied Poernawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this research is to measure performanceÂ RSUD â€œKanjuruhanâ€ Kepanjen Kabupaten MalangÂ by using the conceptÂ Balanced Scorecards referring to four perspectiveÂ whichÂ are, customersÂ perspective, financial perspective, internal business process perspective, and also growth and learningÂ perspective.Â The research used descriptive method by using secondary data among years of 2010 â€“ 2012 and primary data to measure employees and patients satisfaction The results showed that the performance of RSUD